Contextual Narratives Associated With Immunization Services During COVID-19 Disease Outbreak in Chennai, Tamil Nadu - Sucharitha, Sree T; Manoharan, Aravind; Vasudevan, Jaishree; Aaditya Fernando (National Journal of Community Medicine, 2022)
Background: Essential health services including immunization were significantly impacted due to COVID-19 with devastating outcomes in low- and middle-income countries (LMIC). The disruption in immunization services due to global pandemic and measures undertaken at regional levels to overcome need to be studied as pandemic preparedness strategy. Objective: To document the contextual narratives related to immunization services during the Covid-19 disease outbreak by interviewing qualified pediatricians in the field practice area of private tertiary care teaching medical college Methodology: In-depth phone-based interviews were conducted with pediatricians in diverse settings during November 2020 to March 2021. Reflexive thematic analysis was performed, major themes identified, and case studies documented. Results: Pediatricians shared rich experiences related to immunization services impacted due to COVID-19 especially during the earlier months due to imposition of lockdowns leading to discontinuation, disruption of services, decrease in volume of immunizations, modest transition to telehealth service delivery, facility-level changes brought in to ensure immunization services, capacity building measures for upskilling. Conclusions: Contextual narratives revealed in this study provide rich narrative about the disruption of immunization services due to COVID-19. These findings need to be understood and leveraged to be future ready and prevent further disruptions by identifying and scaling up key solutions piloted in this study.